MAPPING CRITICAL MANGROVE LAND USING GEOGRAPHIC INFORMATION SYSTEM TECHNOLOGY IN THE MANDEH AREA - SOUTH PESIR DISTRICT - Pasaribu, Roberto Patar; Pranoto, Aris Kabul; Djari, Anthon Anthonny; -, Amelia Fitrina (Politeknik Kelautan dan Perikanan Dumai, 2024)
The mangrove ecosystem is an ecosystem that has high biodiversity. The mangrove ecosystem has physical functions, including protecting the coast from abrasion and erosion. This ecosystem also functions as a place for spawning, breeding and rearing for various marine organisms. This research aims to determine critical mangrove land using Geographic Information System Technology (GIS) applications and remote sensing techniques as an alternative method for mapping the condition of critical land in the mangrove ecosystem. The research location is in the Mandeh area, Koto XI Tarusan District in Pesisir Selatan Regency, West Sumatra Province. Based on data processing and analysis as well as on-site observations, the critical level of mangrove forests in the Mandeh area is not damaged 119,065 Ha (46.41%), damaged 105,325 Ha (41.05%) and very damaged 32,164 Ha (12.54%).The village areas that were damaged were in Sungai Nyalo Village, while those that were not damaged were in Teluk Raya Village.